Penjelasan dan Analisis Kritikal Doktrin Martabat Tujuh dalam Kerangka Ahli Sunnah Wal Jamaah - Muhammad Khairi Mahyuddin; Ahmad Najaa' Mokhtar; Faudzinaim Badaruddin; Abdull Rahman Mahmood; Wan Haslan Khairuddin; Khairatul Akmar Ab Latif (Mufti of Federal Territory's Office (PMWP), 2024)
Non-Indexed Publication